Pengaruh Cash Position dan Leverage Ratio serta Return On Equity terhadap Dividend Payout Ratio pada Perusahaan Property yang Go Publik - Devi Indra Wahyuni; Michael Hadjaat; Musdalifah Azis (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2018)
Devi Indra Wahyuni, 2017, The Influence of Cash Position and Leverage Ratio Include Return on Equity to Dividend Payout Ratio For Go Public Property Company, on the basis of financial management theory with multiple linear regression analysis using financial statements of 4 property companies from 2007 – 2014. The conclusions of this study: t arithmetic variable CP 0,399 t table 1,96 and significance 0,697 0,05 which means partially CP no significant theory on to DPR on the company’s property go public which the result is Denied. t arithmetic variable DER 2,040 t table 1,96 and significance 003 0,05 which mean partially DER have a significant theory to DPR on the company’s property go public which is the hypothesis was acceptable. t arithmetic variable ROE 0,066 1,96 and significance 0,948 a = 0,05 which means partially ROE no significant theory to DPR on the company’s property go publik which the result is Denied.Keywords:  Cash Position (CP), Debt to Equity Ratio (DER), Return On Equity (ROE) – Dividend Payout Ratio (DPR)